Mother-Child Social Cognition Among Multicultural Families in South Korea - Lee, Joohee; Choi, Kee-Hong (Frontiers in Psychiatry, 2022)
Objective Despite the rapidly growing number of multicultural families in South Korea, factors influencing parenting and mother-child interactions have not been well-understood. To our knowledge, the present study is the first to have examined how maternal social-cognitive capacity is associated with children's social cognition (e.g., theory of mind and emotion recognition) among multicultural families dwelling in South Korea. Methods Forty-seven multicultural mother-child dyads were recruited. The comprehensive measures on social cognition were administered to both the mothers and children, and social functioning and emotion regulation were administered to the children. Results A series of hierarchical regressions indicated that mothers' social cognition significantly explained children's ability to recognize static and dynamic emotional expressions, accounting for 27 and 34% of the variance, respectively. Furthermore, mothers' social cognition was significantly correlated to children's social functioning and emotion regulation. However, mothers' social cognition and children's theory of mind were non-significantly related. Discussion The current study examined the effects of social cognition of immigrant mothers on their children's socio-emotional development. As the findings indicated an important role of maternal factors (i.e., social cognition) for children's social cognition and their functions, psycho-social approaches (e.g., social cognition parenting education and training) should be incorporated in services for multicultural families.